Before the deluge : coping with the floods in a changing climate : IRN dams, rivers and people report 2007 - McCully, Patrick (International Rivers Network BerkeleyUS, 2007)
Deals with coping with floods in a changing climate and notable dam-induced floods. Focuses on how large dams and embankments have worsened India's floods. Highlights advances in flood management.